Economic Costs and Benefits of Imposing Short-Horizon Value-at-Risk Type Regulation - Zhen Shi; Bas J.M. Werker (Tinbergen Institute, 2011)
Regulators often set value-at-risk (VaR) constraints to limit the portfolio risk of institutional investors. For some investors, notably pension funds, the VaR constraint is enforced over a horizon which is significantly shorter than the investment horizon of the investor. Our paper aims to investigate the economic costs and benefits of this kind of regulation. Shorter regulatory constraint, on one hand, enables an institutional investor, like a pension fund, to avoid large losses when the investment environment worsens but, on the other hand, also limits the institutionalinvestor's ability to benefit from an increase in stock prices. We show that the cost introduced by the short-term VaR constraints might over weight the benefitsbrought by such constraints.
Keywords: G11; G23; 330; Portfolio Choice; Value-at-Risk; Pension Funds; Risikomaß; Pensionskasse; Portfolio-Management; Institutioneller Investor; Regulierung; Soziale Kosten